2005
DOI: 10.2174/1381612053381666
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Bacteriocins and their Potential as the Next Generation of Antimicrobials

Abstract: The discovery of penicillin by Fleming in 1928 was an historical milestone in the fight against infectious disease. Over the following fifty years, pharmaceutical companies discovered and developed over 100 antibiotics effective against a wide range of human pathogens. More recently, the dramatic rise in antibiotic-resistant pathogens has stimulated renewed efforts to identify, develop or redesign antibiotics active against these multi-resistant bacteria. This review focuses on such efforts directed at one lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 115 publications
0
47
0
2
Order By: Relevance
“…In the MALDI-TOF mass spectra of the tryptic digests of the 40-and 30-kDa protein, masses representing peptides [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and [2][3][4][5][6][7][8][9][10][11][12][13][14] of P293A were detected, which indicated that the initiating methionine residue was posttranslationally excised from a fraction of the molecules. MALDI-TOF measurements yielded an average molecular mass of 11,832 Da for the intact ␤ chain (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MALDI-TOF mass spectra of the tryptic digests of the 40-and 30-kDa protein, masses representing peptides [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and [2][3][4][5][6][7][8][9][10][11][12][13][14] of P293A were detected, which indicated that the initiating methionine residue was posttranslationally excised from a fraction of the molecules. MALDI-TOF measurements yielded an average molecular mass of 11,832 Da for the intact ␤ chain (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The renewed interest in bacteriocins as antimicrobial agents (5,8,10) and in B. megaterium as an industrial microorganism and cloning host (38) prompted us to revisit megacinogeny of B. megaterium. The interest in B. megaterium is highlighted by the ongoing whole-genome sequencing project (http://www .bios.niu.edu/b_megaterium).…”
mentioning
confidence: 99%
“…Due to the global concern about antibiotic resistance, novel approaches, one being the use of bacteriocins, are being considered (10,11). Colicins, bacteriocins produced by and active against Escherichia coli strains, are receiving renewed attention as an alternative means of preventing various E. coli-associated infections, for example, diarrhea, including serotype O157:H7 (15,22,28,29,30), and postweaning diarrhea and edema disease in swine (33).…”
mentioning
confidence: 99%
“…Lantibiotics have been suggested as a possible alternative to antibiotics for many drug-resistant infections. [8][9][10][11] This is due to their multiple mechanisms of action, broad-spectrum activity against a wide variety of Gram-positive targets, gene-encoded nature (making them excellent templates for bioengineering) and their ability to be delivered to the site of infection. [12][13][14] However, although lantibiotics have been extensively researched, little work has been done to investigate their application to treat mycobacterial diseases.…”
Section: Introductionmentioning
confidence: 99%